Blind Separation of Human Heartbeats and Breathing by the use of a Doppler Radar Remote Sensing - Petrochilos, N.; Rezk, M.; Host-Madsen, A.; Lubecke, V.; Boric-Lubecke, O. (2007 IEEE International Conference on Acoustics, Speech and Signal Processing - ICASSP '07, 2007)
The combined use of a Doppler radar with digital signal processing technique gives an effective non-invasive remote sensing of heart beat signals. Initial results have showed that the proposed technique is very promising in successfully isolating desired heart beat signals from other mobile objects and other distortion effects characterizing the wireless channel. We concentrate in this paper on the harder problem of separating at low SNR the signals from two subjects in the same room. We show that preliminary results obtained by the real analytical constant modulus algorithm (RACMA) and the independent component analysis (ICA) on experimental data are very promising into this goal.